Thermal performance and orientation effect of an inclined cross-cut cylindrical heat sink for LED light bulbs. (December 2016) - Park, Seung-Jae; Jang, Daeseok; Lee, Kwan-Soo
Highlights: The cooling performance of LED bulbs was improved using inclined cross-cut fins. Thermo-flow characteristics around an inclined cross-cut heat sink were investigated. A correlation was suggested to estimate improvement in the cooling performance. A contour map for determining the optimum heat sink shape was suggested. Abstract: An inclined cross-cut cylindrical heat sink was investigated in an attempt to improve the energy conversion and management of LED light bulbs. The thermo-flow characteristics were studied to enhance the cooling performance of a cylindrical heat sink, which is the cooling apparatus used for LED light bulbs. In the inclined cross-cut heat sink, the natural convection flow with an incidence angle had a flow path length that was more stretched in comparison to the flow path length of a straight cross-cut heat sink. Accordingly, the heat transfer rate between the air and fins was increased. When the fins had an inclined angle of 25–30°, the thermal resistance was the smallest. However, when the inclined angle increased to greater than 50°, only the blocking effect was increased and the flow path length was not stretched. Hence, cooling performance was decreased with inclined angles greater than 50°. A correlation predicting the degree of improvement in cooling performance relative to a baseline straight cross-cut heat sink was suggested as a function of heat sink design variables and the installation angle of the heat sink. Finally, a contour map was developed, which can be used to select the optimum heat sink type, with respect to the installation angle of the heat sink and the inclined angle of the fins.